The Critical Review to Evaluate Performance of Ready-Mix Concrete Production Plant - Ghazi, Sara; Al-Zwainy, Faiq Mohammed Sarhan; Manogaran, Gunasekaran Manogaran (Al-Nahrain Journal for Engineering Sciences, 2023)
In Republic of Iraq, ready-mix concrete production plants have been adversely affected by the lack of modern and advanced technology to assess their performance in line with technological advancements. Current evaluation methods rely on traditional approaches and financial measures, yielding unrealistic performance results. To address this problem, there is a need to utilize modern models and methods for performance evaluation. The study’s main objective This was achieved by employing a literature survey methodology and utilizing digital databases such as the Iraqi Scientific Journals website, virtual libraries, and scientific platforms like ScienceDirect, Springer, Google Scholar, and Gate Research between 2015 and 2023. The research study provided a comprehensive overview of performance evaluation, including its definitions, importance, and an introduction to modern models and evaluation methods. The study found that no previous studies have been conducted in Iraq to evaluate ready-mix concrete production plants. However, four studies were found in Egypt, Sudan, and India. The previous similar relevant studies discussed various topics and related studies. Firstly, they discussed the classification, advantages, and disadvantages of concrete mixing plants. Additionally, the previous studies analyzed the factors that most influence the performance of concrete production plants, including laboratory manager efficiency, work team efficiency, communication and relationships within work teams, plant operator, material transportation method, and time and courses. Furthermore, the previous research studies present a comprehensive analysis of all variable data simultaneously using the statistical package for Social Science (SPSS) input stage. The evaluation also extends to the evaluation of laboratories, encompassing plant arrangement, internal quality control systems, and final product quality. The overall evaluation results of previous studies. Indicate that 75% of the concrete production plants failed to meet the required criteria, while only 25% demonstrated satisfactory performance. The study proposed improvements to enhance the performance rate of ready-mix concrete production plants by leveraging the most influential variables, which will be considered in the study.